Search for Genocide Crimes and Evidence in and Around the Territories of the Former NKVD (MGB) Headquarters in Lazdijai and Leipalingis - Čičiurkaitė, Ingrida; Kvizikevičius, Linas (Archaeologia Lituana, 2024)
The main idea of this work is to summarize the data from two independent studies carried out in Lazdijai and Leipalingis in 2021–2023, to share the experience and the features of the research methodology in the search for the remains of the Lithuanian partisans – the clues of the violent crimes that were committed 75–80 years ago. The aim of the article is to identify the pattern of concealment evidence and crimes committed with impunity and systematically by the NKVD troops and their henchmen – the Soviet collaborators. Two tasks are formulated to achieve this goal: firstly, to reveal the theoretical principles of the methodology of the search for evidences applied during the forensic archaeology research in the period 2021–2023 in the search for the remains of the partisans of the Southern region of Lithuania, killed in the period 1945–1952 and possibly hidden in the courtyards of the NKVD headquarters in Lazdijai and Leipalingis and their surroundings, and secondly to summarize the methodology and the results achieved during the field work.